Are the ground reaction forces altered by the curve and with the increasing sprinting velocity? - Millot, B.; Pradon, D.; Cecchelli, G.; Blache, P.; Arnould, A.; Dinu, D.; Slawinski, J (Scandinavian Journal of Medicine & Science in Sports, 2024)
In 200- and 400-m races, 58% of the total distance to cover is in the curve. In the curve, the sprinting performance is decreased in comparison to the straight. However, the reasons for this decreased performance is not well understood. Thus, the aim of this study was to identify the kinetic parameters underpinning the sprinting performance in the curve in comparison to the straight. Nineteen experienced-to-elite curve specialists performed five sprints in the straight and in the curve (radius 41.58 m): 10, 15, 20, 30, and 40 m. The left and the right vertical, anterior-posterior, medial-lateral, and resultant ground reaction forces (respectively Fv, Fa-p, Fm-l and Ftot), the associated impulses (respectively IMPv, IMPa-p, IMPm-l, and IMPtot) and the stance times of each side were averaged over each distance. In the curve, the time to cover the 40-m sprint was longer than in the straight (5.52 ± 0.25 vs. 5.47 ± 0.23 s, respectively). Additionally, the left and the right Fa-p and IMPa-p were lower than in the straight while the left and the right Fm-l increased, meaning that the Fm-l was more medial. The left Fv was also lower than in the straight while the left stance times increased to keep the left IMPv similar to the straight to maintain the subsequent swing time. Overall, the sprinting performance was reduced in the curve due to a reduction in the left and the right Fa-p and IMPa-p, that were likely attributed to the concomitant increased Fm-l to adopt a curvilinear motion.